2012
DOI: 10.1007/s11250-012-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal nematode burden in working equids from humid tropical areas of central Veracruz, Mexico, and its relationship with body condition and haematological values

Abstract: The east coast of Veracruz, Mexico, has an important equine population used for working in rural production systems. The objectives of this study were (1) to calculate the prevalence of tropical working equids (donkeys, mules and horses) infected with gastrointestinal nematodes (GINs) and the GINs involved, and (2) to measure the body condition score (BCS) and haematological values for each working equid and its relationship with faecal worm egg count (EPG). One hundred and forty working equids were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
1
9
2
1
Order By: Relevance
“…Body et al 2011 in roe deer Capreolus capreolus ; Irvine et al 2006 in red deer Cervus elaphus ; Stien et al 2002 in reindeer Rangifer tarandus ; Rubenstein and Hohmann, 1989 in horses; Schulte-Hostedde and Elsasser, 2011 in American mink Neovison vison ), the absence of relationship also appears to be common (e.g. Pilar Valdez-Cruz et al 2013 in equids; Vatta et al 2002 in goats, Scantlebury et al . 2010 in grey squirrel Sciuris carolinensis ; Moretti et al 2014 in toads Rhinella icterica ; Davidson et al 2015 in moose Alces alces ).…”
Section: Introductionmentioning
confidence: 99%
“…Body et al 2011 in roe deer Capreolus capreolus ; Irvine et al 2006 in red deer Cervus elaphus ; Stien et al 2002 in reindeer Rangifer tarandus ; Rubenstein and Hohmann, 1989 in horses; Schulte-Hostedde and Elsasser, 2011 in American mink Neovison vison ), the absence of relationship also appears to be common (e.g. Pilar Valdez-Cruz et al 2013 in equids; Vatta et al 2002 in goats, Scantlebury et al . 2010 in grey squirrel Sciuris carolinensis ; Moretti et al 2014 in toads Rhinella icterica ; Davidson et al 2015 in moose Alces alces ).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in haematological parameters are commonly used in the diagnosis of physiological alterations (Valdéz-Cruz et al , 2013). For example, low RBC values may indicate pathological processes such as anaemia, dehydration, haemorrhage, infections or parasitism, among others (Barros Monteiro et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…As HCT indicates the fraction composed by RBC in the total blood volume, the observed decrease in MCHC, together with an increase in the total RBC count and the lack of changes in HGB levels, appears to indicate that the main haematological alteration induced by E. caproni infection in rats is not only related to the number of RBC but also to their functionality. In this sense, it should be noted that the effect of the intestinal helminth infections on haematological parameters is normally related to elevated parasite loads (Soulsby, 1987; Lassen & Swardson, 1995; Shah et al , 2009; Valdéz-Cruz et al , 2013). The low parasite burden of E. caproni in rats could be the cause of the slight alterations observed in the haematological values.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a study in Mexico found no correlation between fecal worm egg count (EPG) and body condition score in 140 randomly selected working equids. 56 The study concluded that despite the high prevalence and parasite burdens, these equids did not appear seriously affected, and that more emphasis should be placed on other interventions to improve health (eg, nutrition), with anthelmintic treatments reserved only for those equids with the highest EPG or showing clinical signs.…”
Section: Gastrointestinal Nematodesmentioning
confidence: 99%
“…47 Helminthiasis has been documented as a significant issue in working equids, many having a polyparasitism problem. 15,[48][49][50][51][52][53][54][55][56][57] One study 55 revealed the following findings from a 2-year survey into gastrointestinal parasites in working donkeys in Ethiopia: "Coprological examination revealed 99% strongyle, 80% Fasciola, 51% Parascaris, 30% Gastrodiscus, 11% Strongyloides westeri, 8% cestodes and 2% Oxyuris equi infection prevalence. Over 55% of donkeys had more than 1000 eggs per gram of feces (epg).…”
Section: Gastrointestinal Nematodesmentioning
confidence: 99%